(3GdbVGA GdOhdj GdLfGFj ef GdeMGce GdNGUI Edi GdeMceI GdLfGFjI GdOhdjI (B=s International criminal court - (3Gdabj, CMeO MSjfs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3GdbVGA GdOhdj GdLfGFj ef GdeMGce GdNGUI Edi GdeMceI GdLfGFjI GdOhdjI(B) (3hGdPj bGe HJCdjag (B((3CMeO MSjf Gdabj(B) (3aj MhGdj (B(175) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdOhdj GdLfGFj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdaUd GdChd (B: (3fTCI hJWhQ GdbVGA GdOhdj GdLfGFj, GdaUd GdKGfj (B: (3GdShGHb GdbVGFjI dfTCI GdeMceI GdLfGFjI GdOhdjI, GdaUd GdKGdK (B: (3EfTGA GdeMceI GdLfGFjI GdOhdjI GdOGFeI(B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B159-170.s
Keywords: (3GdbGfhf GdOhdj GdLfGFjs; (3GdeMGce GdLfGFjI GdOhdjIs; (3GdeMGce PGJ GdGNJUGU GdNGUs; (3GdbVGA GdOhdj GdLfGFjs